Compressive behavior of high-strength fiber-reinforced concrete - Ricardo Laguardia Justen de Almeida; Guilherme Aris Parsekian; Marco Antonio Carnio (Revista IBRACON de Estruturas e Materiais)
Abstract The present research investigated the compressive behavior of high-strength concrete reinforced with six different types of fiber made of steel, glass and polymer, each one in three volume fractions. Displacement-controlled compressive tests for the complete stress-strain curve were performed over nineteen different mixes and their mechanical properties, such as compressive strength, elastic modulus, peak strain and toughness were analyzed and discussed. Hooked-end and crimped steel fibers provided the greatest gains in mechanical properties, followed by polymeric and glass fibers. Monofilament polymeric fiber and pultruded glass fiber at a volume fraction of 1.00% provided a ductility almost as good as the steel fibers in compression, though. Constitutive models were proposed for each fiber studied and showed good agreement with the experimental results.